PERAN GURU DALAM PELAKSANAAN PENGELOLAAN KELAS PADA KELAS IV DI SDN CISAAT TENGAH KABUPATEN SERANG - Tri Indah Sari; Ujang Jamaludin; Encep Andriana (STKIP Subang, 2023)
The teacher is the most important element in the world of education. In teaching and learning activities, teachers must be able to develop strategies so that students are able to participate in these learning activities, so that the objectives of learning activities can be achieved. It is good classroom management that the teacher can apply so that learning activities run according to purpose. This study aims to determine that teacher’s role in carrying out classroom management planning, the implementation of strategies carried out by the teacher of effective classroom management, and the indicators used to measure the success of classroom management and the evaluation results by the teacher. The research method used is descriptive qualitative by conducting interviews and observations of class IV, V, homeroom teachers and principals at SDN Cisaat Tengah District of Serang, as well as grade IV students. The results of this study indicate that the teacher’s role in implementing classroom management in grade IV is quite good. Where the teacher has been able to apply his role as a good teacher in managing the class, implementing strategic apporoaches and classroom management techinques quite well. But indeed there are still afew shortcomings where the teacher is still very lacking in applying the discussion and debate method.